Peran Bimbingan Agama dalam Meningkatkan Self Esteem pada Lansia - Muhammad Reza Ramadhan (Indonesian Journal of Islamic Counseling, 2023)
This study focuses on the role of religious guidance carried out by Social Workers in Improving Self Esteem in the Elderly at the Social Service Center for Elderly Social Service (Ppslu) Mappakasunggu City of Pare-Pare, the purpose of this study is to determine the role of religious guidance carried out by social workers and to knowing the level of self-esteem in the elderly at the Social Service Center for the Elderly Social Service (PPSLU) Mappakasunggu, Parepare City. The level of self-esteem in the elderly at PPSLU Mapakasunggu Parepare can be classified including high self-esteem which can be concluded that the elderly who receive religious guidance from social workers in the form of advice and enlightenment for the elderly to be aware of carrying out religious orders and the elderly who have strong faith feel confident, feel like themselves and happy to be given religious guidance so as to increase self-confidence (Self-esteem) in the elderly and they can be categorized or grouped as elderly who have high self-esteem because they already have strong confidence in themselves.